The Effect of Wage Levels on Labor Performance in the Islamic Economy Perspective (Case Study on CV. Tedmond Fiber Glass Ahmad Yani street, Air Batu Banyuasin Regency Km.20) - Nova Yuliana (HM Publisher, 2020)
Abstract Wages are the most crucial thing in employment because working people are to get payments that will be used to fulfill their daily needs. If the value of the wages offered by a company is considered insufficient to meet the worker's living needs, then the worker will refuse the job offered. The provision of wages is useful for increasing output and efficiency, and we must be aware of the various difficulties that arise from the incentive pay system. Various problems such as unemployment that is still and continue to grow, the lack of jobs, wages, and welfare of workers who are suffocating, the exploitation of women and child labor are inseparable from these underlying problems. Therefore, the problem is domain and the main responsibility of the state (governments) as a regulator of all aspects of living in a society and society.